Exposure to night‐time light pollution and risk of prolonged duration of labor: A nationwide cohort study. Issue 1 (11th July 2021) - Windsperger, Karin; Kiss, Herbert; Oberaigner, Wilhelm; Leitner, Hermann; Binder, Franz; Muin, Dana A.; Foessleitner, Philipp; Husslein, Peter W.; Farr, Alex
Abstract: Background: Light pollution (LP) is a ubiquitous environmental agent that affects more than 80% of the world's population. This large nationwide cohort study evaluates whether exposure to LP can influence obstetric outcomes. Methods: We analyzed Austrian birth registry data on 717 113 cases between 2008 and 2016 and excluded cases involving day‐time delivery, <23 + 0 gestational weeks, and/or birthweight <500 g, induction of labor, elective cesarean, or cases with missing data. The independent variable, that is, degree of night‐time LP, was categorized as low (0.174 to <0.688 mcd/m 2 ), medium (0.688 to <3 mcd/m 2 ), or high (3 to <10 mcd/m 2 ). Duration of labor and adverse neonatal outcomes served as outcome measures. Results: Cases in regions with high LP (odds ratio [OR], 1.43; 95% confidence interval [CI], 1.30‐1.57) and medium LP (OR, 1.22; 95% CI, 1.14‐1.31) showed increased odds of prolonged labor ( P < .0001 each). Newborns born in regions with high LP (OR, 1.12; 95% CI, 1.07‐1.16) and medium LP (OR, 1.07; 95% CI, 1.04‐1.10) showed increased odds of experiencing adverse outcomes ( P < .0001 each). Preterm delivery <28 + 0 weeks was also associated with the degree of LP ( P = .04). Conclusions: Night‐time LP negatively interferes with obstetric outcomes. The perceived influence of LP as an environmental agent needs to be re‐evaluated to minimize associated health risks.